PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO AND FOUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SIS WA KELAS VIII SMPN 1 GUNUNG TALANG KABUPATEN SOLOK TAHUN PELAJARAN 2013/2014 - KANANDA, VIVI; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
Background of this research is studentâs grade VIII SMPN 1 GunungTalang comprehension of mathematical concepts still low. In that case endence when studentâs are less active in the learning process. The purpose of this research is to know how studentâs activity in the learning process by using the power of two and four strategy and to know what is studentâs comprehension of mathematical concept at grade VIII SMPN 1 GunungTalang by using the power of two and four strategy better than convensional model. Kind of this research is experimental researcd,becides research plan is random on subject. The population is studentâsat grade VIII SMPN 1 GunungTalang academic year 2013/2014. To take sample in this research is randomly so that, the researchergotten grade VIII.5 as experiment class and VIII.4 as control classÂ the instrumentation is used in this research isÂ comprehension test of mathematical concept. Type of test is used type essay with realibilitas test is . Tecnique of analysis data is t-test one side by using software minitab therefore, the final analysis with a = 0,05 be obtained P-value = 0,003, because P-value minus for a, so hipothesis is accepted in this research. So that it can be concluded that studentâs comprehension of mathematical concept is treated by using the power of two and four strategy better than studentâs comprehension of mathematical concepts is treated by using convensional model at grade VIII SMPN 1 GunungTalang.